Use of the isometamidium Elisa to measure serum concentrations of the drug in Jersey dairy cattle in Kenya - Eisler, M.C.; Maloo, S.H.; Peregrine, A.S.; Holmes, P.H.; Thorpe, W.R. (OAU/STRC, 1995)
Isometamidium chloride is the most important chemoprophylactic agent used in the control of African bovine trypanosomiasis, although breakdowns in prophylaxis have been observed in the field. It is not usually apparent whether these breakdowns are due to inadequate drug dosage regimens, or to the Development of drug-resistance in trypanosomes. A recently developed enzyme-linked immunosorbent assay (ELISA) for the detection of isometamidium provides a means of resolving this question in field situations. This was tested using sera from Jersey cattle under isometamidium prophylaxis (0.5 mgkg-1 body weight by intramuscular injection at three-monthly intervals), which were exposed to natural tsetse challenge in coastal Kenya. Although isometamidium could be quantified in the sera of the treated cattle, the incidence of trypanosomiasis, determined by the presence of parasites in the buffy coat, was not lower in these cattle than in untreated controls. It was concluded that the dosage regimen was inadequate to prevent infections occurring, perhaps because the drug concentrations were too low during the last third of inter-treatment intervals. It was recommended that isometamidium prophylaxis at 1.0 mgkg-1 body weight should be evaluated.